HUBUNGAN SPIRITUALITAS DAN INTERAKSI SOSIAL DENGAN KUALITAS HIDUP LANSIA - Setyowati, Sri; Isnaeni, Yeni; Rahayu, Bety Agustina; Supatmi, Supatmi; Pranawati, Erma; Kumalasari, Dian Novita (Coping: Community of Publishing in Nursing; Vol 12 No 2 (2024): April 2024DO - 10.24843/coping.2024.v12.i02.p06, 2024)
A person enters the elderly stage (elderly) starting at the age of 60 years and above and is at risk of being susceptible to various health problems. The changes experienced by the elderly can hinder the elderly's spiritual and social interactions, thereby affecting the quality of life of the elderly. The aim of this research is to determine the relationship between spirituality and social interaction and quality of life in the elderly. This type of research is non-experimental research with a correlational study design using a cross-sectional approach. The population was 60 elderly people who were active at the Matahasi Posyandu Timbulharjo Sewon Bantul with a total sampling technique. Data sampling was taken using a questionnaire. Data were analyzed using ordinal logistic regression analysis. The research results showed that the majority of respondents were young, elderly women with a final education level of elementary school. The majority of respondents have a good level of spirituality, less social interaction and quality of life in the good category. The results of the analysis test show the conclusion that there is a relationship between the level of spirituality and quality of life (0,000) and there is a relationship between social interaction and quality of life (0,013).